The Jesus you can't ignore : what you must learn from the bold confrontations of Christ - MacArthur, John, 1939- (Nashville, Tenn. : Thomas Nelson, 2008)
Renowned Bible teacher and bestselling author MacArthur reintroduces the compelling and often unsettling passion and fierceness of Jesus' ministry.
Prologue -- Introduction -- When it's wrong to be "nice" -- Two Passovers -- A midnight interview -- This man speaks blasphemies -- Breaking the sabbath -- Hard preaching -- Unpardonable sin -- Woe -- Epilogue.
Includes bibliographical references (pages 213-218).
Keywords: Jesus Christ -- Person and offices; Apologetics; Truth -- Religious aspects -- Christianity; Christian life